Potensi Sumber Daya Alam dalam Mengembangkan Sektor Pariwisata di Indonesia - Bonaraja Purba; Elsa Aurel A. Situmorang; Deyren Firmansyah; Tamaria br.Sidebang; Tasya Amelia Manurung (Masyarakat Ekonomi Syariah Bogor, 2024)
This analysis aims to ascertain how natural resources can contribute to the growth of the Indonesian tourism industry. Information is collected, and storytelling strategies are used qualitatively.The data analysis technique that this research uses is a literature review approach to understand and analyze concepts. The research results show that simultaneously, the developing natural resource potential of the Indonesian tourism industry has a positive and significant influence on Indonesia's natural resources and the tourism sector in Indonesia.